Colleges and schools-College of Agricultural Sciences and Technology-Industrial Technology 050
Victor Roznovsky, presidents of the Home Builders Association of the San Joaquin Valley, presents a $1000 scholarship check to Dr. Noeman A. Baxter, president of California State University, Fresno, and William H. Livingston, professor of industrial arts and technology. The grant, provided by the National Associated of Home Builders, will be awarded to a student or students preparing for careers in the home building or related industry through the university's construction course option in the Department of Industrial Arts and Technology.